Amino acids and fatty acids composition in mass‐cultured Teleaulax amphioxeia strains with notable potential for rotifer (Brachionus plicatilis) enrichment. Issue 3 (3rd May 2020) - Kim, Hyung Seop; Kim, Jong Hyeok; Jo, Soo‐Gun; Rho, Jung‐Rae; Yih, Wonho
Abstract: To evaluate the nutritional quality of the Teleaulax / Plagioselmis / Geminigera (TPG) clade species over the conventional prey species of the Rhodomonas / Rhinomonas / Storeatula (RHO) clade for the enrichment of a rotifer, Brachionus plicatilis, two strains of Teleaulax amphioxeia ( TA ), CR‐MAL07 and CR‐MAL08‐02, and a Chroomonas sp. strain CR‐MAL10 from Korean coastal waters were mass cultured in 500 L photobioreactors. When harvested from the stationary growth phase, the composition of all three macronutrients and three n‐3 highly unsaturated fatty acids (UFAs) exhibited large deviations among strains and culture media. The composition of essential amino acids and UFAs was higher in CR‐08‐02 by up to 1.1 and 22.2 times, respectively, than that in a commercially available Chlorella sp. strain. For the enrichment of B. plicatilis cultures previously grown with the Chlorella concentrates, high‐density cultures of CR‐08‐02 were offered. After a 3‐hr enrichment, the compositions of eicosapentaenoic acid, n‐3 FA (fatty acids), and n‐6 FA in B. plicatilis increased by 331, 19.5, and 10.48%, respectively, which might reflect the relevant quality compositions in the TA cells. Thus, TA in the TPG clade can be another novel type of prey to enrich rotifer cultures for the marine larviculture.